(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The article analyzes the works of G. S. Skovoroda, which highlights issues of economic and social development of predominantly Sloboda Ukraine. His views on economics have been elucidated, the meaning of the concept of "related" work has been explored, which is considered by the thinker as an important means of achieving the well-being and happiness of every person. The vision of G. S. Skovoroda to build a future, just society where good and prosperity will reign is revealed. The purpose of the article. Тhe purpose of the study is to study the socio-economic views of GS Skovoroda, to clarify their content. According to the purpose of the research the following tasks are outlined: stages of formation of economic views; the concept of "related" labor as the basis of life and its limitations; ways to build a just and happy society. Results. A society where each person realizes his natural endowments in kindred labor and enjoys it can be brought to life through education and self-discovery that serves as a universal vehicle for moral restructuring of the world. Material relations and relationships between people are governed by the observance of moral principles. The basis of morality and justice is related work, which is beneficial to society as a whole. The very process of its implementation is enjoyable. Conclusiоns. The economic views of GS Skovoroda were formed together with the outlook, with an understanding of social processes, the search for ways to solve their challenges, explaining the meaning of human life and ways to obtain happiness. The statements were made more concrete, and the interpretation, which was a heuristic means of obtaining new conclusions, was deepening. In the 60s of the 18th century. GS Skovoroda is mainly interested in the issues of moral principles of practical human behavior, believes that the forces of good, which resist evil, are in the man himself and given to him by nature. They need to be known, opened and put into action. To overcome evil, you must lead a lifestyle worthy of man. The unity of good and beauty is the source of human happiness. Beauty is organically associated with kindness